Calculation of Last Closed Drift Shells for the 2013 GEM Radiation Belt Challenge Events. Issue 11 (21st November 2018) - Albert, J. M.; Selesnick, R. S.; Morley, S. K.; Henderson, M. G.; Kellerman, A. C
Abstract: Radiation belt behavior is often analyzed in terms of adiabatic invariants, of which the third roughly characterizes the radial distance of particle drift shells. The outermost, or last closed drift shell, can be an important boundary for numerical modeling, especially for drift‐averaged treatments such as three‐dimensional diffusion codes. Here we discuss calculation of the last closed drift shell, using the widely used International Radiation Belt Environment Modeling (IRBEM) Library, the LanlGeoMag code, and a guiding center code named AFRL‐Shell, in conjunction with a variety of current magnetic field models. We present results for the four events in 2013, comprising the radiation belt challenge organized by the Quantitative Assessment of Radiation Belt Modeling focus group of the Geospace Environment Modeling (GEM) program. Key Points: Several codes to calculate L* in realistic magnetic field models are presented Methods for finding last closed drift shells with these codes are discussed Results for four GEM radiation belt challenge events, using a variety of magnetic field models, are compared